PagDET2 promotes cambium cell division and xylem differentiation in poplar stem - Wang, Yao; Hao, Yi; Guo, Yakun; Shou, Huixia; Du, Juan (Frontiers in Plant Science, 2022)
Secondary growth of the woody trees stem was governed by meristematic cell divisions and differentiation in the vascular cambium. Multiple hormonal signals and endogenous developmental programs are involved in the regulation of vascular cambium activity. Brassinosteroids (BRs) significantly promotes secondary stem growth and wood formation in poplar trees. However, the underlying regulatory mechanisms of BRs within the vascular tissue remain largely unknown. Genetic and anatomical approaches were used here to elucidate the role of PagDET2, the rate-limiting enzyme for BRs biosynthesis, in the regulation of secondary vascular cambium activity in Populus. This study showed the elevated endogenous castasterone levels in tree stems through overexpressing PagDET2, which resulted in promoted secondary stem growth with enhanced cambium cell activity, xylem differentiation, and wood formation. RNA-seq analysis revealed that genes involved in BRs responses and vascular cambium cell division, differentiation, SCW synthesis and regulation are up-regulated in response to increased BR levels of PagDET2 overexpression lines. This study characterized vascular cambium cell activity changes in response to elevated BRs and profiled candidate BRs responsive genes that function in vascular cambium cell division and xylem differentiation in poplar trees.